Adsorptive and Membrane-Type Separations: A Bibliographical Update (1998) - Martyn S. Ray (Adsorption Science & Technology)
This paper continues a series of annual bibliographic updates of the published literature (since 1985) on adsorptive and membrane-type separations (see Ray 1990–1998). This paper provides a useful and quick reference source to the 1998 journal literature (from the 50 most important chemical engineering journals) for researchers in this area. The papers included here have been divided into the following subject groups: theory; design data; adsorbents; PSA and cyclic systems, and applications; liquid-phase adsorption; ion exchange, chromatography and related separations; membranes; and membrane-type separations. A new edited book (Dabrowski 1999) concerned with adsorption and related separations also contains extensive bibliographies prepared by this author. A complete bibliographic listing of the chemical engineering journal literature from 1959 to 1998 (with subsequent six-monthly updates) is available on a CD-ROM database and full details can be obtained from the author.